KUALITAS PELAYANAN KESEHATAN PASIEN RAWAT INAP PENGGUNA BPJS DI RUMAH SAKIT ORTOPEDI SURAKARTA : KUALITAS PELAYANAN KESEHATAN PASIEN RAWAT INAP PENGGUNA BPJS DI RUMAH SAKIT ORTOPEDI SURAKARTA - Chindy Wijanarko; Noor Alis Setyadi (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2025)
The quality of health services is an important factor to describe patient satisfaction. Especially for BPJS patients who often face various challenges to achieve optimal service. The study aims to describe the quality of health services at Prof. Dr. R. Soeharso Surakarta Hospital. This study uses a quantitative descriptive approach. The sample in the study was 100 patients taken using a purposive sampling technique. The collection of research data used a questionnaire whose validity and reliability have been tested with the results of Cronbach's Alpha Tangible 0.943 (reliable), reliability 0.969 (reliable), Responsiveness 0.977 (reliable). Empathy 0.909 (reliable), and Assurance 0.966 (reliable). The results of the study stated that the majority of respondents had a good view regarding satisfaction with various aspects of the health services provided. This reflects the hospital's commitment to providing safe and caring services to BPJS patients. Therefore, this study is expected to be the basis for the development of more optimal and sustainable services.